Reversal of Alpha-Synuclein Fibrillization by Protein Disulfide Isomerase - Serrano, Albert; Qiao, Xin; Matos, Jason O.; Farley, Lauren; Cilenti, Lucia; Chen, Bo; Tatulian, Suren A.; Teter, Ken (Frontiers in Cell and Developmental Biology, 2020)
Aggregates of α-synuclein contribute to the etiology of Parkinson's Disease. Protein disulfide isomerase (PDI), a chaperone and oxidoreductase, blocks the aggregation of α-synuclein. An S-nitrosylated form of PDI that cannot function as a chaperone is associated with elevated levels of aggregated α-synuclein and is found in brains afflicted with Parkinson's Disease. The protective role of PDI in Parkinson's Disease and other neurodegenerative disorders is linked to its chaperone function, yet the mechanism of neuroprotection remains unclear. Using Thioflavin-T fluorescence and transmission electron microscopy, we show here for the first time that PDI can break down nascent fibrils of α-synuclein. Mature fibrils were not affected by PDI. Another PDI family member, ERp57, could prevent but not reverse α-synuclein aggregation. The disaggregase activity of PDI was effective at a 1:50 molar ratio of PDI:α-synuclein and was blocked by S-nitrosylation. PDI could not reverse the aggregation of malate dehydrogenase, which indicated its disaggregase activity does not operate on all substrates. These findings establish a previously unrecognized disaggregase property of PDI that could underlie its neuroprotective function.